Incidence and Course of Inhibitors among Patients with Classic Hemophilia - Kasper, Carol K. (Thrombosis and Haemostasis, 1973)
The incidence of known inhibitors among patients with severe classic hemophilia seen at Orthopaedic Hospital, Los Angeles, increased from 4.8 percent in 1967 to 7.8 percent in 1972. Possible reasons for the increase may include : 1. selective referral of patients with inhibitor to this center and 2. a three-fold increase in the frequency of plasma product infusion and an eight-fold increase in the factor VIII units infused per year per patient. The incidence of inhibitors was highest among young children; in 1972, 14.6 percent of children under age 10 years and 6 percent of older patients had inhibitors. Several patients developed inhibitors in late adolescence or adulthood, some after little exposure to blood products, and others after many more than a hundred accumulated days of exposure. Anamnestic responses to plasma product infusions occurred in all children under age 4 with inhibitors and all older patients with pre-infusion inhibitor titers of at least two units. Some adolescent or adult patients with low-titer inhibitors received plasma products on several occasions without developing higher titers but later responded to another infusion with a marked rise in titer.